Hubungan antara Pathological Gambling dengan Perilaku Merokok pada Dewasa Awal di Kota Padang - Awaliyah, Diniati; Nurmina, Nurmina (Lembaga Yasin AlSys, 2025)
Addictive behaviors such as pathological gambling and smoking are two common mental and physical health issues among individuals in early adulthood. This study aims to examine the relationship between pathological gambling and smoking behavior among young adults in Kota Padang. A quantitative method with a correlational design was employed. The study involved 350 participants aged 18 to 25 years, selected using purposive sampling. Instruments included the Gambling Symptom Assessment Scale (G-SAS) to measure the level of pathological gambling (Grant et al., 2013) and the Glover-Nilsson Smoking Behavior Questionnaire (GN-SBQ) to assess behavioral dependence on smoking (Faradhillah & Dewi, 2018a). Data were analyzed using Pearson correlation test with IBM SPSS 25. The results indicate a significant positive relationship between pathological gambling and smoking behavior, with a significance value of p = 0.000 (p < 0.05) and a correlation coefficient of r = 0.845. These findings suggest that individuals with high levels of pathological gambling also tend to exhibit high levels of smoking behavior. The implications underscore the need for preventive interventions targeting dual addictive behaviors in early adulthood, particularly in urban areas such as Kota Padang, to mitigate the long-term negative impacts on mental and physical health.